Predicting Food Waste Reduction Behavior Among Students in Higher Education Institutions - Valentin, Alvin Patrick M (Archīum Ateneo, 2024)
Purpose This study aims to determine and analyze the predictors of food waste reduction intention and behavior among higher education institutions (HEIs) using an extended version of the theory of planned behavior (TPB). Design/methodology/approach This study empirically tested an extended TPB model through regression analyses using data obtained through an online survey. Findings Attitude toward food waste reduction, subjective norms, perceived behavioral control and food waste knowledge predicted intention to reduce food waste. Furthermore, the intention to reduce food waste predicted food waste reduction behavior. Research limitations/implications The results imply that extending the TPB by adding food waste knowledge significantly predicted food waste reduction intention and behavior. Practical implications The study identified factors that predict food waste reduction behavior and suggested ways to influence Filipino students in HEIs to reduce food waste. Originality/value The findings support the inclusion of food waste knowledge to the TPB in predicting food waste reduction intention and behavior among students in HEIs.